Pengembangan Aplikasi Penelusuran Alumni STAI DDI Pangkajene Sidrap Berbasis Web - Jumiyati, Muh. Rizal Samad, Maryati (LLDikti Wilayah IX Sulawesi dan Gorontalo, 2019)
This study aims (1) To develop a web-based application for tracing the alumni of the Sekolah Tinggi Agama Islam (STAI) DDI Pangkajene Sidrap. (2) To determine the application of the Web-based DDI Pangkajene Sidrap Alumni Tracing application. This type of research is research and development (R&D) using the waterfall software engineering development model, with four stages, namely analysis, design, coding, and testing. The research subjects were 35 alumni respondents. Data were analyzed using descriptive statistics in the form of data presentation with tables, calculation of means and percentages. The results of the study show that (1) the development of the application for Tracing of STAI DDI Pangkajene Sidrap alumni uses the waterfall model R&D method, the development stage begins with the analysis, design, coding, and testing stages. (2) The results of the small group trial show that the alumni tracing application is in a good category, thus it can be implemented on a larger scale. The application for tracing the alumni of STAI DDI Pangkajene Sidrap is very helpful in the process of managing alumni data and providing information about alumni data. The campus can process and coordinate its alumni.